Role of magnetic resonance imaging and ultrasonography in diagnosis and followup rheumatoid arthritis in hand and wrist joints - Waleed M. Hetta; Sherin M. Sharara; Gehan Ali Gouda (The Egyptian Journal of Radiology and Nuclear Medicine, 2018)
Purpose: To compare the role of ultrasonography and MRI in the diagnosis of synovitis involving wrist and hand joints in Rheumatoid arthritis patients. Materials and methods: Fifty patients with rheumatoid arthritis involving the wrist were subjected to hand and wrist ultrasonography Doppler and MRI and the results are compared and correlated during the period from December 2015 to January 2017. Results: Ultrasound detected synovial hypertrophy (pannus) in 42 wrist joints while MRI detected it in 46. Power Doppler detected increased vascularity within 30 wrist joints (60%), MRI detected synovial enhancement within 38 (76%). Power Doppler detected synovial activity (vascularity) in MCP joints of 13 patients and MRI detected synovial activity (enhancement) in MCP joints of 9 patients. Ultrasound detected erosions in 35 wrist and 27 MCP joints and MRI detected erosions in 37 wrist and 25 MCP joints. Ultrasound detected tendinitis in 9 extensor tendons and MRI detected tendinitis in 8 tendons. Conclusion: We found a significant correlation between power Doppler ultrasonography and MRI in the detection of signs of inflammation and bone destruction in the wrist and hand joints in rheumatoid arthritis, which raise the potential importance of power Doppler study in the assessment and monitoring of disease activity as a reliable non-invasive method. Keywords: Rheumatoid artheritis, MRI, Ultrasonography